Analysis of total burn surface area from bleve fireball impact at dynamic parameter condition: article - Mohd Zaidi, Aiman Hazim; Aiman Hazim Bin Mohd Zaidi, Dr Zulkifli Ab Rashid, Mohd Zaidi (2019)
Feyzin disaster during 1966 in France will always leave a big mark in engineering industry as it involved many casualties. The disaster would make a perfect example of case study on impact of BLEVE fireball towards nearby occupants. The methodology to investigate BLEVE’s characteristic, fireball’s impact toward the effect of TBSA to human during Feyzin incident is by using BLEVE’s dynamic model in the analysis. All scenarios involved during the analysis such as sphere tank design, chronology of accidents, and other relevants input is based on ARIA Feyzin incident report. The probability of occupants to get caught on fire and suffers different type of burns are determined with different distance from fireball. TBSA charts and age from JP Bull is simplified to RSM model, to determine the burn surface area on human’s body.